2021
DOI: 10.18502/ijph.v50i7.6636
|View full text |Cite
|
Sign up to set email alerts
|

Fha Deficient Bordetella pertussis Isolates in Iran with 50 Years Whole Cell Pertussis Vaccination

Abstract: Background: Bordetella pertussis, a highly contagious respiratory. Notably, the resurgence of pertussis has recently been associated with the lacking production of vaccine virulence factors. This study aimed to screen pertactin (Prn) and filamentous hemagglutinin (Fha) production in Iran with 50 years' whole cell vaccine (WCV) immunization program. Methods: Overall, 130 B. pertussis isolates collected from Pertussis Reference Laboratory of Iran during 2005-2018. Real-time PCR was performed by targeting I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 47 publications
1
2
0
Order By: Relevance
“…Tehran as a capital and Eastern Azarbayjan, a north-western province, each had three isolates. These two provinces had the most B. pertussis isolates in recent years as reported previously [ 6 , 15 ]. During 2012–2015 around 112 B. pertussis isolates collected from different provinces in Iran [ 6 ] showing low isolation rate of B. parapertussis in the country with 50 years whole cell pertussis vaccination history.…”
Section: Resultssupporting
confidence: 56%
See 2 more Smart Citations
“…Tehran as a capital and Eastern Azarbayjan, a north-western province, each had three isolates. These two provinces had the most B. pertussis isolates in recent years as reported previously [ 6 , 15 ]. During 2012–2015 around 112 B. pertussis isolates collected from different provinces in Iran [ 6 ] showing low isolation rate of B. parapertussis in the country with 50 years whole cell pertussis vaccination history.…”
Section: Resultssupporting
confidence: 56%
“…The emergence of Prn negative B. parapertussis isolates could be a global concern especially in countries with ACV immunisation program since this phenotype can easily escape vaccine pressure by not expressing Ptx and Prn as two main components of ACVs. We previously showed that no mutation or disruption was found in the prn gene in current circulating predominant B. pertussis isolates in Iran and no Prn negative isolate was reported from Iran with WCV immunisation program [ 6 , 15 , 16 ]. Here, western blot was carried out to investigate the expression of Prn in our B. parapertussis isolates and it showed all seven isolates express Prn and confirmed the WCV immunisation did not affect phenotype evolution of this species in Iran.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation